Autophagic secretion of mitochondria (ASM): an alternative way for getting rid of damaged mitochondria. Issue 2 (1st February 2023) - Tan, Hayden Weng Siong; Lu, Guang; Shen, Han-Ming
ABSTRACT: PINK1-PRKN/Parkin-mediated mitophagy represents an important mitochondrial quality control (MQC) pathway that clears damaged/dysfunctional mitochondria. Although the conjugation of mammalian Atg8-family proteins (mATG8s) to phosphatidylethanolamine (PE) is a defining step in autophagy, its role in mitophagy remains unclear. In our recent study, we found that the mATG8 conjugation system is not required for PINK1-PRKN-mediated mitochondria clearance. Instead, mATG8 conjugation system-independent mitochondria clearance relies on secretory autophagy, a process we term as the autophagic secretion of mitochondria (ASM). As ASM results in the spurious activation of the CGAS-STING1 pathway, we propose that defects in mATG8 lipidation may promote inflammation through ASM.